2020
DOI: 10.1073/pnas.2008209117
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced receptor binding of SARS-CoV-2 through networks of hydrogen-bonding and hydrophobic interactions

Abstract: Molecular dynamics and free energy simulations have been carried out to elucidate the structural origin of differential protein–protein interactions between the common receptor protein angiotensin converting enzyme 2 (ACE2) and the receptor binding domains of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) [A. E. Gorbalenyaet al.,Nat. Microbiol.5, 536–544 (2020)] that causes coronavirus disease 2019 (COVID-19) [P. Zhouet al.,Nature579, 270–273 (2020)] and the SARS coronavirus in the 2002–2003 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
416
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 317 publications
(453 citation statements)
references
References 46 publications
34
416
1
1
Order By: Relevance
“…using FEP. 47 In addition, this mutation was shown to be among the five mutations that produce a super affinity ACE2 binder based on SARS-COV RBD. 6 Alanine mutations at residues Y449, G447 and E484 increased the motion in is the reason for higher binding energy of mutant Y489A than wild-type complex.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…using FEP. 47 In addition, this mutation was shown to be among the five mutations that produce a super affinity ACE2 binder based on SARS-COV RBD. 6 Alanine mutations at residues Y449, G447 and E484 increased the motion in is the reason for higher binding energy of mutant Y489A than wild-type complex.…”
Section: Discussionmentioning
confidence: 98%
“…52 The critical role of interface residues and residues are computationally investigated here and in other articles and the results of all the studies indicate the importance of these residues for the stability of the complex and finding hotspot residues for the interaction with receptor ACE2. 47,[52][53][54] It is interesting to note the role of shown there is a correlation between higher binding affinity to receptor and higher infection rate by coronavirus. [55][56][57][58] High binding affinity for some mutants such as T478I could be the reason for higher human-to-human transmission rate in regions where these mutations are found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, atomistic-level comparison is needed between these two viruses. A recent study found that the hydrogen bonding network and the hydrophobic interactions are major dominating forces that are responsible for enhanced binding in SARS-CoV-2 19 . Till now most of the studies focus on the search for new vaccines and drug molecules against COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, as we demonstrate in this study, ACE2 is a potent inhibitor of neutralizing antibody binding to the SARS-CoV-2 spike protein receptor binding domain, and this may relate to why short-lived antibody responses are a hallmark component of SARS-CoV-1 infections in many patients, whereby SARS-CoV-2 exhibits as much as 10-15x stronger binding to ACE2 than SARS-CoV-1 and would likely exhibit even stronger antibody maturation issues according to this hypothesis. 40,41,42,43 Therapeutics that mimic ACE2 and shield this key epitope are likely to bias antibody formation towards off-target sites, which could contribute to antibody-dependent enhancement (ADE), vaccine-associated enhanced respiratory distress (VAERD), and a host of other immunological issues upon repeat viral challenge. 44,45,46,47,48,49,50,51,52,52 With SARS-CoV-1, a marked lack of peripheral memory B cell responses was observed in patients 6 years following infection.…”
Section: Discussionmentioning
confidence: 99%